KERAGUAN DAN KEPASTIAN HUKUM DALAM KONSUMSI PRODUK KULINER MODERN: PERSPEKTIF KAIDAH AL-YAQĪN LĀ YUZĀLU BI AL-SYAKK - Zulfitriana; Hasna Mardanus; Imran Anwar Kuba; Achmad Musyahid (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study uses a qualitative approach with a desk research approach and a normative analysis of jurisprudence proposals. Data were obtained from classical literature of the endowment of jurisprudence, rules of jurisprudence, as well as contemporary sources such as scientific journals and halal fatwas. The results of the study show that the rules of certainty do not go away by siyak, provide a strong epistemological basis for determining the law of the origin of food sweetness, so that doubts without strong evidence cannot cancel out the halal status that was previously believed. This rule is relevant in answering the problem of modern culinary consumption that is full of siofat elements, while emphasizing the importance of verification through halal certification and wisdom (ihtiat).